2009
DOI: 10.1371/journal.pone.0005535
|View full text |Cite
|
Sign up to set email alerts
|

The Oxytocin Receptor (OXTR) Contributes to Prosocial Fund Allocations in the Dictator Game and the Social Value Orientations Task

Abstract: BackgroundEconomic games observe social decision making in the laboratory that involves real money payoffs. Previously we have shown that allocation of funds in the Dictator Game (DG), a paradigm that illustrates costly altruistic behavior, is partially determined by promoter-region repeat region variants in the arginine vasopressin 1a receptor gene (AVPR1a). In the current investigation, the gene encoding the related oxytocin receptor (OXTR) was tested for association with the DG and a related paradigm, the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
204
6
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(226 citation statements)
references
References 62 publications
(64 reference statements)
13
204
6
3
Order By: Relevance
“…Indeed, there are numerous examples of smallscale candidate gene studies that report significant associations with behavioral traits that could not be replicated. For instance, Israel et al (2009) report an association between a variant of the OXTR gene and the dictator game. Apicella et al (2010) fail to replicate this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are numerous examples of smallscale candidate gene studies that report significant associations with behavioral traits that could not be replicated. For instance, Israel et al (2009) report an association between a variant of the OXTR gene and the dictator game. Apicella et al (2010) fail to replicate this association.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the reported association would not have reached the accepted genome-wide significance level of p \ 5 9 10 -8 . Associations are often reported to be false positives if a set of candidate genes is selected, while not all relevant genes and SNPs are considered (e.g., Apicella et al 2010;Becker et al 2007;Israel et al 2009;Lang et al 2004;Lesch et al 1996;Vormfelde et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…For example, oxytocin receptor gene (OXTR) variation is associated with prosocial behavior (Israel et al, 2009), empathy and stress reactivity (Rodrigues et al, 2009), pair bonding (Walum et al, 2011), parenting behavior (Bakermans-Kranenburg and van Ijzendoorn, 2011), emotional loneliness (Lucht et al, 2009), and functional links between hypothalamic and limbic system activity in emotional face processing (Tost et al, 2010). Epigenetic variation in methylation of the OXTR gene is similarly associated with neural responses to ambiguous social stimuli (Jack et al, 2012), autism and callous-unemotional traits (Gregory et al, 2009;Kumsta et al, 2013).…”
Section: Embodiment Of Individual Differences In Attachmentmentioning
confidence: 99%
“…Independent studies have reported evidence that variation in OXTR increases susceptibility for ASC [36][37][38][39][40][41], although there has been some heterogeneity in these findings [42]. Persons diagnosed with ASC often exhibit gross impairments in social functioning [43]. Furthermore, OXTR risk variants for ASC have been associated with individual differences in healthy populations in social behaviours of trust [42] and empathy [44,45].…”
Section: Introductionmentioning
confidence: 99%